Colloids - Types, Preparation and Applications 2021
DOI: 10.5772/intechopen.95351
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Iron Oxide Colloids for Environmental Applications

Abstract: This chapter deals with magnetic colloids with catalytic properties for the treatment of polluted waters and the efficient production of fuel alternatives. This kind of materials presents great advantages such as high surface/volume ratio, reproducibility, selectivity, ability to be magnetic harvested, functionalizable surfaces (e.g. with tunable pores and selective chelators deposited on them), high efficiencies and reusability. In particular, this chapter will consider the case of magnetic iron oxide colloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Then, the mixture was overhead stirred at 100 rpm, and nitrogen (9.5 L/min) was flowed through the stirrer guide for 1.5 h (stirring and nitrogen flow were maintained throughout the process). The reactor (isolated externally with glass wool) was heated at 670 W until reaching 195 • C (1 h); then, the reflux refrigeration started, and the power was reduced to 244 W in order to maintain the temperature at approximately 200 • C for 2 h. Finally, the mixture was heated at full power (1300 W) up to the boiling temperature (~285 • C) for a variable amount of time (5,15,30,60, or 120 min). Immediately after, the stirring was stopped, and the heating mantle removed in order to quench the reaction while maintaining the nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the mixture was overhead stirred at 100 rpm, and nitrogen (9.5 L/min) was flowed through the stirrer guide for 1.5 h (stirring and nitrogen flow were maintained throughout the process). The reactor (isolated externally with glass wool) was heated at 670 W until reaching 195 • C (1 h); then, the reflux refrigeration started, and the power was reduced to 244 W in order to maintain the temperature at approximately 200 • C for 2 h. Finally, the mixture was heated at full power (1300 W) up to the boiling temperature (~285 • C) for a variable amount of time (5,15,30,60, or 120 min). Immediately after, the stirring was stopped, and the heating mantle removed in order to quench the reaction while maintaining the nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
“…Many applications have been envisaged for magnetic nanoparticles (MNPs) in recent decades, most of which are in the biomedical field, for example, their use as contrast agents in magnetic resonance imaging [ 1 , 2 ] or for cancer treatment through their capacity to generate heat under alternating magnetic fields (AMF) [ 3 ], among others. In the last decade, new applications related to biocatalysis have indicated that these MNPs not only can support enzymes or biomolecules efficiently, which can be easily separated by means of a magnetic field, but they are also able to activate them [ 4 , 5 ] when subjected to an AMF [ 6 , 7 , 8 ]. The local heat generation at the MNP surface and its control at the nanoscale are hot research topics in the nanotechnology field [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, iron oxide is an inexpensive material and is largely used in many industrial processes such as the synthesis of ammonia and dehydrogenation of organic substrates, while there is a lot of active research dedicated to the study of iron oxide nanocatalysts for the degradation of organic dyes [22], among other environmental applications [23]. Their magnetic properties allow catalyst recovery by magnetic separation, interesting for example in the field of wastewater treatment, and can be selectively heated upon application of alternating magnetic fields, which can improve the yield of different reactions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several nanomaterials have been developed over the past few decades, including magnetic nanoparticles (Fe 3 O 4 ) and carbon-based nanomaterials such as graphite, graphene, carbon nanotubes, and hydrophobic organoclay, and employed for oil spill remediation . Recently, the use of Fe 3 O 4 for oil spill remediation has gained much attention due to its high performance, low cost, biocompatibility, and magnetic properties . Furthermore, the surface modification of Fe 3 O 4 with suitable materials enhances their stability and improves their dispersion and interaction with crude oil components, thus improving their performance for oil spill uptake. , In our earlier work, different ionic liquids , and natural compounds were investigated for Fe 3 O 4 surface modification and applied to oil spill remediation.…”
Section: Introductionmentioning
confidence: 99%
“…27 Recently, the use of Fe 3 O 4 for oil spill remediation has gained much attention due to its high performance, low cost, biocompatibility, and magnetic properties. 28 Furthermore, the surface modification of Fe 3 O 4 with suitable materials enhances their stability and improves their dispersion and interaction with crude oil components, thus improving their performance for oil spill uptake. 29,30 In our earlier work, different ionic liquids 30,31 and natural compounds 32−34 were investigated for Fe 3 O 4 surface modification and applied to oil spill remediation.…”
Section: Introductionmentioning
confidence: 99%